2016
DOI: 10.1039/c6nr03543d
|View full text |Cite
|
Sign up to set email alerts
|

Decoupling the shape parameter to assess gold nanorod uptake by mammalian cells

Abstract: The impact of nanoparticles (NPs) upon biological systems can be fundamentally associated with their physicochemical parameters. A further often-stated tenet is the importance of NP shape on rates of endocytosis. However, given the convoluted parameters concerning the NP-cell interaction, it is experimentally challenging to attribute any findings to shape alone. Herein we demonstrate that shape, below a certain limit, which is specific to nanomedicine, is not important for the endocytosis of spherocylinders by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 48 publications
(92 reference statements)
0
14
0
Order By: Relevance
“…Work by Chithrani et al [ 41 ] suggested that as the AR of AuNRs increases, the cellular uptake decreases. However, a more recent study by Kinnear et al [ 67 ] considered the uptake of AuNRs with almost identical properties except AR (AuNR volume, zeta potential, colloidal stability, among others) by an A549 lung cancer cell line. They observed no correlation between AuNR aspect ratio and cellular uptake, below an AR of 7.2 ( nm, SPR nm), suggesting that the AuNRs used in this study may show no size dependence on cellular uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Work by Chithrani et al [ 41 ] suggested that as the AR of AuNRs increases, the cellular uptake decreases. However, a more recent study by Kinnear et al [ 67 ] considered the uptake of AuNRs with almost identical properties except AR (AuNR volume, zeta potential, colloidal stability, among others) by an A549 lung cancer cell line. They observed no correlation between AuNR aspect ratio and cellular uptake, below an AR of 7.2 ( nm, SPR nm), suggesting that the AuNRs used in this study may show no size dependence on cellular uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Kinnear et al synthesized different gold rods of varied aspect ratios and studied their interaction with macrophages and epithelial cells. 140 Rods of B10-90 nm in length and with small aspect ratios (o5), revealed similar uptake efficiencies in both cells. In contrast, nanorods with higher aspect ratio (45) were preferentially internalized by epithelial cells, whereas the uptake in macrophages revealed to be shape independent.…”
Section: Shapementioning
confidence: 90%
“…Specifically, these were citrate-stabilized gold nanospheres (Citrate-GNS) and polymer-functionalized gold nanospheres coated either with PEG (PEG-GNS) or a combination of PEG and PVA (PEG/PVA-GNS), as well as PEGylated gold nanorods (PEG-GNR). 16,17 Gold core diameters were measured by transmission electron microscopy (TEM) as 13.4 ± 2.3, 15.7 ± 1.9, and 14.6 ± 1.8 nm for citrate-GNS, PEG-GNS, and PEG/ PVA-GNS, respectively. Dimensions of the PEG-GNR were measured at 57 ± 12 nm × 15 ± 3 nm, giving an aspect ratio of 3 ± 0.8 ( Figure 1A and Table 1).…”
Section: Gnps With Different Polymer Coatings and Shapesmentioning
confidence: 99%